Aerobic oxidation of 5-hydroxymethylfurfural to 5-hydroxymethyl-2-furancarboxylic acid and its derivatives by heterogeneous NHC-catalysis. Issue 46 (7th November 2018) - Brandolese, Arianna; Ragno, Daniele; Di Carmine, Graziano; Bernardi, Tatiana; Bortolini, Olga; Giovannini, Pier Paolo; Pandoli, Omar Ginoble; Altomare, Alessandra; Massi, Alessandro
Abstract : Heterogeneous NHC-catalysis is an effective synthetic platform for the production of bio-based furan derivatives. Abstract : The application of the oxidative system composed of a heterogeneous triazolium pre-catalyst, iron(ii ) phthalocyanine and air is described for the selective conversion of 5-hydroxymethylfurfural (HMF ) into the added-value 5-hydroxymethyl-2-furancarboxylic acid (HMFCA ). The disclosed one-pot two-step procedure involved sequential oxidative esterifications ofHMF to afford a polyester oligomer having hydroxyl and carboxyl terminal groups ( M w = 389–1258), which in turn was hydrolyzed by a supported base (Ambersep 900 OH) to yieldHMFCA in 87% overall yield. The same strategy was adopted for the effective synthesis of ester and amide derivatives ofHMFCA by nucleophilic depolymerization of the oligomeric intermediate with methanol and butylamine, respectively. The utilization of the disclosed oxidative system for the direct conversion ofHMF and furfural into their corresponding ester, amide, and thioester derivatives is also reported.